2017
DOI: 10.3389/fpsyg.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Time-Preference Tests Fail to Predict Behavior Related to Self-control

Abstract: According to theory, choices relating to patience and self-control in domains as varied as drug use and retirement saving are driven by generalized preferences about delayed rewards. Past research has shown that measurements of these time preferences are associated with these choices. Research has also attempted to examine how well such measurements can predict choices, but only with inappropriate analytical methods. Moreover, it is not clear which of the many kinds of time-preference tests that have been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Alterations in TD are associated with a range of psychiatric conditions and problematic behaviors, including addiction, substance abuse and attention‐deficit hyperactivity disorder (Amlung et al, 2019; Bickel et al, 2019; Jackson & MacKillop, 2016; Wiehler & Peters, 2015). TD exhibits stability over weeks ( r = .91; Simpson & Vuchinich, 2000), months ( r = .77–.80; Arfer & Luhmann, 2017), and even 1 year ( r = .71; Kirby, 2009), and across different testing environments (Bruder et al, 2021; Odum, 2011). TD is therefore regarded as a trait‐like characteristic (Smith & Hantula, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in TD are associated with a range of psychiatric conditions and problematic behaviors, including addiction, substance abuse and attention‐deficit hyperactivity disorder (Amlung et al, 2019; Bickel et al, 2019; Jackson & MacKillop, 2016; Wiehler & Peters, 2015). TD exhibits stability over weeks ( r = .91; Simpson & Vuchinich, 2000), months ( r = .77–.80; Arfer & Luhmann, 2017), and even 1 year ( r = .71; Kirby, 2009), and across different testing environments (Bruder et al, 2021; Odum, 2011). TD is therefore regarded as a trait‐like characteristic (Smith & Hantula, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to favor smaller-but-sooner over larger-but-later rewards, known as temporal discounting, is common across animals (Kalenscher & Pennartz, 2008) and humans (Peters & Büchel, 2011). The individual degree of temporal discounting varies profoundly and appears stable across time (Simpson & Vuchinich, 2000; Arfer & Luhmann, 2017; Kirby, 2009) and across different testing environments (Bruder et al, 2021; Odum, 2011). Thus, discounting is regarded as a trait-like characteristic (Smith & Hantula, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several variables come to mind, such as personality features and dispositional traits, which should be included in future studies. In this sense, patience could be a mediator variable affecting FPR1 and FPR2, such as previous studies suggested [73]. Considering that patience implies willingness to sacrifice current satisfaction for future rewards, it might result in higher preparedness for retirement.…”
Section: Discussionmentioning
confidence: 89%